Teaching medical students about the impacts of climate change on human health - Jason Gomez (Elsevier, 2021)
Climate change is among the greatest threats to human health, yet most medical schools fail to adequately teach students about its impact. To address this educational gap, we designed and implemented a new elective course for Stanford medical students, “The Impact of Climate Change on Human Health.” Students (40/74, 54% response rate) evaluated its effectiveness by completing a pre/post-course survey that measured changes in their beliefs, attitudes, and knowledge about the health effects of climate change. We found significant increases in students' beliefs about the need for climate change education and related physician responsibilities. Intentions to change personal behaviors and apply new knowledge in future clinical practice also significantly increased. Our findings illustrate the importance of a medical school course on climate science and health. Additionally, we describe the curriculum design and program evaluation of our course.